Endophytes Fungi Associated With a Water Hyacinth of Eichhornia Crassipes (Mart.) Solms - Govindan, Venkatesan; Gunasekaran, Arun (International Journal of Scientific Research in Biological Sciences, 2020)
Nineteen endophytes fungal species were isolated from leave and petiole of an aquatic hyacinth weed plant of Eichhornia crassipes. These plants were collected from a freshwater pond in different months at Mannargudi in Tamil Nadu. Among these two belonging to Ascomycetes, four fungal species belonging to Coelomycetes and eleven Hyphomycetes beside to two sterile forms. These endophytic fungi were studied shows fewest colonies that some of the distinct occupying the leaf and petiole tissue. Commonly isolated genera from both month and tissue were Alternaria alternata, Aspergillus niger, Colletotrichum cloeosporioides, Curvularia lunata, Fusarium oxysporum, Penicillium sp. Phomopsis sp., and Yeast form. This study revealed that fungal diversity varied with tissue types and by host plant in representative two months. This diversity of fungi has been assessed to vary depending on the specificity of the tissue. According to the RPO statistical analysis, Hyphomycetes fungi have been dominated by both tissues. Similarly, according to the CF% calculation, more no. of fungal colonies has been isolated from leaf tissue. Assumed, that these distributed fungi have been dependent on tissues specificity.